Answer:
A. 7
Step-by-step explanation:
Since the triangle sides are not defined, therefore let the base side have the 12 unit and one of the slant side be 7 unit.
Therefore height of the triangle, h can gotten from the Pythagoras theorem as thus:
7² = (12/2)² + h²
49 = 36 + h²
h² = 49 - 36 = 13
h = √13
knowing the height of the triangle, we can apply same rule to the other unknown slant side, x as thus:
x² = (12/2)² + h²
x² = 36 + 13 = 49
x = √49
x = 7
Line 1:
Expanding the vertex form, we have
x² + 2·1.5x + 1.5² - 0.25 = x² +3x +2
Expanding the factored form, we have
x² +(1+2)x +1·2 = x² +3x +2
Comparing these to x² +3x +2, we find ...
• the three expressions are equivalent on Line 1
Line 2:
Expanding the vertex form, we have
x² +2·2.5x +2.5² +6.25 = x² +5x +12.5
Expanding the factored form, we have
x² +(2+3)x +2·3 = x² +5x +6
Comparing these to x² +5x +6, we find ...
• the three expressions are NOT equivalent on Line 2
The appropriate choice is
Line 1 only
Y=4x+4
I think this is it u just have to simplify to get it to y=mx+b
Answer is in a photo. I couldn't attach it here, but I uploaded it to a file hosting. link below! Good Luck!
bit.
ly/3a8Nt8n